Bjurböle L/LL4 ordinary chondrite properties studied by Raman spectroscopy, X-ray diffraction, magnetization measurements and Mössbauer spectroscopy - Maksimova, A.A. (2020)
Bjurböle L/LL4 ordinary chondrite was studied using scanning electron microscopy with energy dispersive spectroscopy, Raman spectroscopy, X-ray diffraction, magnetization measurements and Mössbauer spectroscopy. The phase composition and the relative iron fractions in the iron-bearing phases were determined. The unit cell parameters for olivine, orthopyroxene and clinopyroxene are similar to those observed in the other ordinary chondrites. The higher contents of forsterite and enstatite were detected by Raman spectroscopy. Magnetization measurements showed that the temperature of the ferrimagnetic-paramagnetic phase transition in chromite is around 57 K and the saturation magnetic moment is ~7 emu/g. The values of the 57Fe hyperfine parameters for all components in the Bjurböle Mössbauer spectrum were determined and related to the corresponding iron-bearing phases. The relative iron fractions in Bjurböle and the 57Fe hyperfine parameters of olivine, orthopyroxene and troilite were compared with the data obtained for the selected L and LL ordinary chondrites. The Fe2+ occupancies of the M1 and M2 sites in silicate crystals were determined using both X-ray diffraction and Mössbauer spectroscopy. Then, the temperatures of equilibrium cation distribution were determined, using two independent techniques, for olivine as 666 K and 850 K, respectively, and for orthopyroxene as 958 K and 1136 K, respectively. Implications of X-ray diffraction, magnetization measurements and Mössbauer spectroscopy data for the classification of the studied Bjurböle material indicate its composition being close to the LL group of ordinary chondrites.